Radical romanticism, violent cuteness, and the destruction of the world. Issue 3 (20th August 2018) - van der Drift, Mijke
ABSTRACT: In this paper I will make the case that the bodily change is a strategy for the destruction of the world. Radical romanticism, I will argue, is an ethical praxis of tactile engagement producing futures, without subsuming agential differences into a singular form. I will make the case that attention to cuteness and touch can turn into strategies for emergent practices beyond violent domination. I will discuss cuteness through the theorization of Tripthi Pillai and Sianne Ngai. Then turn to a reading of Neelu Bhuman's Love Letter/Prema Lekha, which I will let culminate through resonance with Sharon Patricia Holland's engagement with quotidian racism, in a proposal for radical romanticism. This reading will shown to be the overture for the destruction of the world through an articulation of transsomatechnics via the work of Denise Ferreira da Silva. Somatechnics can be envisioned as strategy of ethics supported by María Lugones' world travelling. The end of the world might emerge from brokenness as Nat Raha discusses.